2020
DOI: 10.1371/journal.pone.0228282
|View full text |Cite
|
Sign up to set email alerts
|

Using Andersen’s behavioral model of health care utilization in a decentralized program to examine the use of antenatal care in rural western Ethiopia

Abstract: BackgroundIn Ethiopia, most women do not make the minimum number of antenatal care (ANC) visits recommended by WHO. This study modeled predisposing, enabling, need, and external environmental factors in the utilization of decentralized health facilities for ANC services in rural western Ethiopian communities. MethodsA community-based, cross-sectional study was conducted in Gida Ayana Woreda (District) among 454 women. Data were collected through structured questionnaires. Multinomial logistic regression was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 39 publications
2
28
0
2
Order By: Relevance
“…It is a well-validated and most widely adopted theoretical framework that permits systematic identification of factors that influence individual decisions to use or not to use available health care services [ 40 ]. Several studies have used this conceptual model to study health care utilization [ 41 , 42 , 43 , 44 ]. The selection of study variables to be included in this study was done based on the purpose of this research, previously published literature from low- and middle-income countries [ 45 , 46 ], and the availability of information regarding the relevant variables.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a well-validated and most widely adopted theoretical framework that permits systematic identification of factors that influence individual decisions to use or not to use available health care services [ 40 ]. Several studies have used this conceptual model to study health care utilization [ 41 , 42 , 43 , 44 ]. The selection of study variables to be included in this study was done based on the purpose of this research, previously published literature from low- and middle-income countries [ 45 , 46 ], and the availability of information regarding the relevant variables.…”
Section: Methodsmentioning
confidence: 99%
“…It is a well-validated and most widely adopted theoretical framework that permits systematic identification of factors that influence individual decisions to use or not to use available health care services [40]. Several studies have used this conceptual model to study health care utilization [41][42][43][44].…”
Section: Explanatory Variablesmentioning
confidence: 99%
“…After multiple iterations over 3 decades, Andersen's model took health behavior explicitly into account [10]. While the model has been used in LMICs to look at outcomes such as antenatal care and contraceptive use, and studies have shown the effects of demographic and socio-economic factors, enabling factors, and perceived need on health services utilization [11,12], the insights offered in terms of behavioral processes themselves have been limited. Moreover, the extent to which this model has contributed to the incorporation of social and behavior change (SBC) in the design, implementation, and evaluation of health systems interventions is not obvious.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the ramifica-F. Namrata, Z. G. Loewy tions can be underpinned using Andersen's 2014 theory of health service use [14]. This comprehensive model explains the interaction between people, the external environment, and the healthcare systems [15]. Multiple factors, including cultural, economic, social, and individual characteristics, primarily predispose people to accessing healthcare [14].…”
Section: Approach To Resolve Disparities: Integrating the Conceptual Frameworkmentioning
confidence: 99%
“…The model also posits that the enabling factors, including health services organization, governance, and financing, may decrease or increase access to healthcare [14]. Patients' behavioral factors, including professional and personal, also influence access to healthcare services [15]. The model is pertinent because it links patient satisfaction as desired outcomes to health; this theory is therefore relevant to understanding access to dental healthcare [14].…”
Section: Approach To Resolve Disparities: Integrating the Conceptual Frameworkmentioning
confidence: 99%